Fertility outcomes in women experiencing severe complications after surgery for colorectal endometriosis. Issue 3 (5th January 2018) - Ferrier, C; Roman, H; Alzahrani, Y; d'Argent, E Mathieu; Bendifallah, S; Marty, N; Perez, M; Rubod, C; Collinet, P; Daraï, E; Ballester, M
Abstract: STUDY QUESTION: What are the fertility outcomes in women wishing to conceive after experiencing a severe complication from surgical removal of colorectal endometriosis? SUMMARY ANSWER: The pregnancy rate (PR) among women who wished to conceive after a severe complication of surgery for colorectal endometriosis was 41.2% (spontaneously for 80%, after ART procedure for 20%). WHAT IS KNOWN ALREADY: While the long-term benefit of surgery on pain and quality of life is well documented for women with colorectal endometriosis, it exposes women to the risk of severe complications. However, little is known about fertility outcomes in women experiencing such severe postoperative complications. STUDY DESIGN, SIZE, DURATION: This retrospective cohort study included women who experienced a severe complication after surgery for colorectal endometriosis between January 2004 and June 2014, and who wished to conceive. A total of 53 patients met the inclusion criteria. The fertility outcome was available for 48 women, who were therefore included in the analysis. The median follow-up was 5 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: All the women underwent complete removal of colorectal endometriosis. Postoperative severe complications were defined as grades III–IV of the Clavien–Dindo classification. Fertility outcomes, PR and cumulative pregnancy rate (CPR), were estimated. MAIN RESULTS AND THE ROLE OF CHANCE: Most women experienced a grade IIIb complication (83.3%). Of 48 women, 20 became pregnant (overall PR: 41.2%); spontaneously for 16 (80%) and after ART procedure for 4 (20%). The median interval between surgery and first pregnancy was 3 years. The live birth rate was 14/48 (29.2%). The 5-year CPR was 46%. A lower CPR was found for women who experienced anastomotic leakage (with or without rectovaginal fistula) ( P = 0.02) or deep pelvic abscess (with or without anastomotic leakage) ( P = 0.04). LIMITATIONS REASONS FOR CAUTION: Due to a lack of information, no sub-analysis was done to investigate other parameters potentially impacting fertility outcomes. WIDER IMPLICATIONS OF THE FINDINGS: The PR for our population was slightly lower to that observed in the literature for women who experience such surgery without consideration for the occurrence of complications. However, 'severe complications' covers a range of conditions which are likely to have a very different impacts on fertility. Even if the PR and CPR appear satisfactory, septic complications can negatively impact fertility outcomes. Rapid ART may be a good option for these patients. STUDY FUNDING/COMPETING INTEREST(S): No funding was required for the current study. Pr H. Roman reported personal fees from Plasma Surgical Inc. (Roswell, GA, USA) for participating in a symposium and a masterclass, in which he presented his experience in the use of PlasmaJet ® . None of the other authors declared any conflict of interest. TRIAL REGISTRATION NUMBER: N/A.